Health Plan Performance Measurement: Does it Affect Quality of Care for Medicare Managed Care Enrollees? - M. Kate Bundorf; Kavita Choudhry; Laurence Baker (SAGE Publishing, 2008)
Although the objective of provider performance measurement is to improve quality of care, little evidence exists on whether it has this effect. This study examines the implementation of mandatory quality reporting for Medicare managed care (MMC) plans. We compare utilization rates of performance-measured services for Medicare beneficiaries who were and were not enrolled in these plans before and after the program's introduction. We find that the use of measured services increased among both MMC and fee-for-service beneficiaries after the adoption of performance measurement. Our results provide no evidence that performance measurement increased quality of care among MMC enrollees.